The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/2179-8087.019115
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Films Produced from the Bleached Pinus sp. Kraft Pulp

Abstract: This study investigates the physical and mechanical properties of nanostructured films produced from Pinus sp. kraft pulp. To obtain the nanocellulose, the bleached kraft pulp was submitted to six different grinding regimes: two, five, ten, 20, 30, and 40 passes through the grinder. The influence of the number of passes was evaluated through the films’ physical and mechanical properties. The results show that the nanofibers reduced the thickness and considerably increased the density values of the fabricated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…The bleached MFC had an increase in ICr after the mechanical defibrillation process, which resulted in greater exposure of the fibrils than in the cellulose fiber sample, increasing its ICr, but did not cause fiber degradation and tearing to the point of affecting the index. Lengowski et al (2018) and Viana et al (2019) found ICr values close to 80 % for unbleached pine cellulose fiber, near those found in work, which is consistent with other published studies.…”
Section: Table 3: Crystallinity Index Of Cellulose Fibers and Suspens...supporting
confidence: 92%
“…The bleached MFC had an increase in ICr after the mechanical defibrillation process, which resulted in greater exposure of the fibrils than in the cellulose fiber sample, increasing its ICr, but did not cause fiber degradation and tearing to the point of affecting the index. Lengowski et al (2018) and Viana et al (2019) found ICr values close to 80 % for unbleached pine cellulose fiber, near those found in work, which is consistent with other published studies.…”
Section: Table 3: Crystallinity Index Of Cellulose Fibers and Suspens...supporting
confidence: 92%
“…Too much exudate can cause skin maceration or infection, on the contrary, allowing the wound to become very dry can slow down the healing process (Chinga-Carrasco and Syverud 2014; Gustaite et al 2015;Basu et al 2017a). The water absorption determined by the Cobb method was 78 g m -2 , which is similar to the value of 85.7 g m -2 obtained by Viana et al (2019) for 60 g m -2 nanocellulose film. The smaller grammage of the films compared to Viana et al (2019) allows for similar absorption, however more pliable, which was beneficial from a dressing usage point of view.…”
Section: Materials Characterizationmentioning
confidence: 54%
“…Those parameters were established based on previous studies (Viana et al 2019). Before, the material presented a liquid aspect and, after passing through the mill, the resulting material presents a gel aspect.…”
Section: Cellulose Micro Brils Preparationmentioning
confidence: 99%
“…Nanocellulose thin lms were prepared with 2 % of total solid content based on the literature (Viana et al 2019). The procedure comes from the protocol 2540 G from APHA (1998) and it is described in the SI.…”
Section: Nanocellulose Lmsmentioning
confidence: 99%